KOBIECY KOMIKS AUTOBIOGRAFICZNY - Gajewska, Grażyna (Studia Europaea Gnesnensia, 2017)
The article is concerned with the works of Polish female comic book artists. I advance the thesis that in their artistic work harbours autobiographical elements which constitute an important element of the whole. I begin the article by clarifying certain notions, namely women's, feminist and autobiography as they may be ambiguously construed. Also, the works in which such autobiographical themes are present are divided into three focus groups: 1. Revisionist representation of history, 2. Emotions, sex life, motherhood, 3. Relations of women with the world, the family, and oneself.